Electronic components and manufacturing method thereof

The electronic component design with a ceramic body and external electrode, utilizing a base layer with communicating pores and a metal layer extending through these pores, addresses the adhesion issue in conventional components, ensuring strong bonding and reducing peeling risks.

JP7619438B2Active Publication Date: 2025-01-22MURATA MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023508810
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-02-21
Publication Date
2025-01-22
Estimated Expiration
2042-02-21

AI Technical Summary

Technical Problem

The bonding force between the porous external electrode (base layer) and the plating layer (metal layer) in conventional electronic components is insufficient, leading to a risk of peeling, especially as components become smaller.

Method used

An electronic component design with a ceramic body and external electrode featuring a base layer in contact with the ceramic body, where the base layer has pores communicating to the interface, and a metal layer extending through these pores to enhance adhesion, achieved through a manufacturing method involving a raw material composition of glass precursor, metal salt, organic polymer, and solvent, followed by heat-treatment and electrolytic plating.

Benefits of technology

The solution provides excellent adhesion between the base layer and metal layer, reducing the risk of peeling and enhancing bonding strength, particularly in smaller components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619438000003
    Figure 0007619438000003
  • Figure 0007619438000004
    Figure 0007619438000004
  • Figure 0007619438000005
    Figure 0007619438000005
Patent Text Reader

Abstract

Provided is an electronic component: in which an external electrode includes a base layer and a metal layer; and which exhibits excellent adhesion between the base layer and the metal layer. This electronic component comprises a ceramic body and an external electrode provided on the surface of the ceramic body. The external electrode includes: a base layer which is in contact with the surface of the ceramic body; and a metal layer formed on the surface of the base layer. The base layer has pores that communicate between the base layer surface and the base layer boundary with the ceramic body. A portion of the metal layer extends to the boundary via the pores, and voids in the base layer constitute 1.5% by volume or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electronic component and a manufacturing method thereof, and more particularly to an electronic component including a ceramic body and external electrodes provided on a surface of the ceramic body, and a manufacturing method thereof. [Background technology]

[0002] An electronic component may include external electrodes for mounting on a circuit board, etc. In a conventional general electronic component, the external electrodes are formed by applying a conductive paste to a ceramic body, firing the body, forming a base layer derived from the conductive paste, and plating the base layer.

[0003] The external electrodes of the multilayer chip inductor are made of a porous material with many pores. For example, Patent Document 1 describes that the porosity (air porosity) of the external electrodes is preferably about 10% to 30%, and that the average pore size of the pores is preferably 0.3 μm to 4.0 μm. The pores are impregnated with a resin that is the same material as the buffer material interposed between the sintered body and the internal electrodes. A plating layer is formed on the surface of the external electrodes.

[0004] The external electrodes are formed by firing, and are made of a composition that creates many pores after firing. For example, it is described that by using a metal paste whose main component is Ag, which is composed of 73 wt% Ag particles (spherical particles, average particle size 0.5 μm), 4 wt% glass frit (ZnO-B2O3-SiO2), 10 wt% ethyl cellulose, and 13 wt% 1:1 mixture of butyl carbitol acetate and ethyl carbitol, the glass frit is gasified during firing to form a porous metal member. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-244116 A Summary of the Invention [Problem to be solved by the invention]

[0006] In Patent Document 1, the bonding strength between the porous external electrode (underlayer) and the plating layer (metal layer) is insufficient, and there is a risk of the metal layer peeling off, particularly when electronic components are miniaturized. Therefore, an object of the present invention is to provide an electronic component comprising a ceramic body and an external electrode, wherein the external electrode includes a base layer and a metal layer and has excellent adhesion between the base layer and the metal layer, and to provide a method for manufacturing the electronic component. [Means for solving the problem]

[0007] According to one aspect of the present invention, An electronic component comprising a ceramic body and an external electrode provided on a surface of the ceramic body, the external electrode includes a base layer in contact with a surface of the ceramic body, and a metal layer formed on the surface of the base layer, the underlayer has pores extending from a surface thereof to an interface with the ceramic body, a portion of the metal layer extends through the pore to the interface; There is provided an electronic component, wherein the voids in the underlayer are 1.5% by volume or less.

[0008] According to another aspect of the present invention, A method for manufacturing an electronic component including a ceramic body and external electrodes provided on a surface of the ceramic body, comprising the steps of: the external electrode includes a base layer in contact with a surface of the ceramic body, and a metal layer formed on the surface of the base layer, the base layer including a base metal and glass, The method comprises: a step of preparing a raw material composition including a glass precursor as a raw material of the glass, a metal salt as a raw material of the base metal, an organic polymer as a thickener, and a solvent having a vapor pressure of 0.1 kPa or more at room temperature, applying the raw material composition to a surface of the ceramic body, and then performing a heat treatment to form a base layer; and forming the metal layer on the surface of the underlayer by electrolytic plating. Effect of the Invention

[0009] According to the present invention, there is provided an electronic component including a ceramic body and an external electrode, the external electrode including an underlayer and a metal layer, and excellent adhesion between the underlayer and the metal layer. Also, according to the present invention, there is provided a method for manufacturing such an electronic component. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2A is a schematic cross-sectional view of an exemplary electronic component in an embodiment of the present invention, and FIG. 2B is an enlarged schematic cross-sectional view taken along the XX plane of FIG. [Diagram 2] 2 is an enlarged schematic cross-sectional view of a base layer of an electronic component and its vicinity in an embodiment of the present invention. FIG. [Diagram 3] 1 shows a TEM image of a cross section of an underlayer formed on a surface of a ceramic body (before plating treatment) in an embodiment of the present invention. [Figure 4] FIG. 1A is a schematic cross-sectional view of an exemplary electronic component in a first embodiment of the present invention, and FIG. 1B is an enlarged schematic cross-sectional view taken along the YY plane of FIG. [Diagram 5] 1 shows a STEM image of a cross section of an underlayer in a sample produced in Example 1 of the present invention. [Figure 6] 1 shows the results of examining the distribution of Si by EDX analysis of a TEM image of a cross section of an underlayer in a sample produced in Example 1 of the present invention. [Figure 7] 1 shows the results of examining the distribution of Ag by EDX analysis of a TEM image of a cross section of an underlayer in a sample prepared in Example 1 of the present invention. [Figure 8] 1 shows the results of examining the distribution of Ni by EDX analysis of a TEM image of a cross section of the underlayer in a sample produced in Example 1 of the present invention. [Figure 9]1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Comparative Example 1 of the present invention. [Figure 10] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Example 2 of the present invention. [Figure 11] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Example 3 of the present invention. [Figure 12] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Example 4 of the present invention. [Figure 13] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Example 5 of the present invention. [Figure 14] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Example 6 of the present invention. [Figure 15] 1 shows an SEM image of the exposed surface (before plating treatment) of the underlayer formed in Comparative Example 2 of the present invention. [Figure 16] 1 is a graph showing Ni plating film thickness versus integrated current in Example 7 of the present invention and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The electronic component of this embodiment is an electronic component comprising a ceramic body and an external electrode provided on a surface of the ceramic body, the external electrode including a base layer in contact with the surface of the ceramic body and a metal layer formed on the surface of the base layer, the base layer having pores connecting its surface to the interface with the ceramic body, a portion of the metal layer extending through the pores to the interface, and voids in the base layer being 1.5 volume % or less.

[0012] As long as the electronic component comprises a ceramic body and external electrodes provided on the surface of the ceramic body, there are no particular limitations on the shape, dimensions, and material of the ceramic body, and the number, arrangement, and shape of the external electrodes. The ceramic body may or may not have internal electrodes embedded therein, and if present, the internal electrodes are electrically connected to the external electrodes in an appropriate manner.

[0013] The electronic components that can be used in this embodiment can be, for example, surface mount type, particularly chip components, and more specifically, can be capacitors such as multilayer ceramic capacitors, inductors (coils) such as wire-wound inductors, film inductors, and multilayer inductors, resistors such as chip resistors, transistors, LC composite components, and the like.

[0014] Illustratively, the electronic component 10 of this embodiment may be a multilayer ceramic capacitor as shown in Fig. 1(a), and includes a ceramic body 1 including a ceramic portion 3 made of a ceramic material and internal electrodes 5a, 5b facing each other via the ceramic portion 3, and external electrodes 9a, 9b provided on the surface of the ceramic body 1 and electrically connected to the internal electrodes 5a, 5b, respectively. More specifically, the internal electrodes 5a, 5b are embedded in the ceramic body 1, stacked so as to be alternately exposed from opposing end faces of the ceramic body 1, and electrically connected to the external electrodes 9a, 9b, respectively. However, the electronic component 10 of this embodiment is not limited to the one exemplified in Fig. 1(a), and may be various electronic components as described above.

[0015] 1(b), in the electronic component 10 of this embodiment, an external electrode 9 (corresponding to the external electrodes 9a, 9b illustrated in FIG. 1(a)) includes an underlayer 6 in contact with the surface of the ceramic body 1 (mainly corresponding to the ceramic part 3 illustrated in FIG. 1(a)), and a metal layer 8 formed on the underlayer 6. In the ceramic body 1 including the internal electrodes 5a, 5b shown in FIG. 1(a), the underlayer 6 may be formed so as to be in contact with the internal electrodes 5a, 5b exposed from the end faces of the ceramic body 1, and the metal layer 8 may be formed on the underlayer 6.

[0016] The material constituting the metal layer 8 is not particularly limited as long as it is conductive, and examples thereof include nickel (Ni), copper (Cu), and tin (Sn). The metal layer 8 may be a single layer or a multilayer. The thickness of the metal layer 8 is not particularly limited, and may be, for example, 100 nm or more and 10 μm or less.

[0017] Although not limiting this embodiment, more specifically, the metal layer 8 may include a single layer of nickel (Ni) layer in contact with the surface of the underlayer 6. When the metal layer 8 is multi-layered, it may be included as an innermost layer (a layer in contact with the surface of the ceramic body 1). For example, the multi-layered metal layer 8 may be a laminate (Ni / Cu / Sn layers) including a nickel layer (Ni layer), a copper layer (Cu layer), and a tin layer (Sn layer) in this order from the base layer 6 onwards.

[0018] The nickel layer can effectively prevent "solder erosion," which is the loss of metal material contained in the underlayer 6 when the electronic component is soldered to a circuit board or the like (more specifically, a land or the like) for mounting. The tin layer can constitute the outermost layer of the external electrode 9, which improves "solder wettability" when the electronic component is soldered to a circuit board or the like for mounting, and can provide high strength at the solder joint. The copper layer can be provided as appropriate depending on the application of the electronic component.

[0019] As shown in FIG. 2, the underlayer 6 has pores P that communicate from its surface 6a to the interface (rear surface 6b) with the ceramic body 1. In FIG. 2, the pores P that communicate from the surface 6a to the rear surface 6b in a planar (two-dimensional) manner are shown, but in reality, a large number of pores P exist three-dimensionally inside the underlayer 6, and many of them communicate from the surface 6a to the rear surface 6b. Therefore, it is difficult to directly confirm the communicating pores by image analysis. If the underlayer 6 is subjected to EDX analysis after the metal layer 8 is formed, and an element (e.g., Ni) that constitutes the metal layer 8 exists inside the underlayer 6, it can be inferred that the pores P exist there. Note that, when the metal layer 8 is formed on the surface 6a of the underlayer 6, a part of the metal layer 8 is also formed inside the pores, so that many of the pores P do not remain as voids in the final electronic component 10 product.

[0020] A part of the metal layer 8 passes through the pores P of the base layer 6 and extends to the interface (rear surface 6b) between the base layer 6 and the ceramic body 1. As a result, the metal layer 8 extends across the entire thickness of the base layer 6 like the roots of a tree, providing a high anchor effect on the base layer 6 and making the metal layer 8 less likely to peel off.

[0021] In this embodiment, the voids in the underlayer 6 are low, at 1.5% by volume or less. In this specification, the term "voids" refers to the spaces remaining inside the pores P after a portion of the metal layer 8 has expanded. A low porosity means that most of the pores P are filled with the metal layer 8. When most of the pores P are filled with the metal layer 8, the bonding strength between the base layer 6 and the metal layer 8 is further increased. In other words, when the porosity is sufficiently low, 1.5% or less, the bonding strength between the base layer 6 and the metal layer 8 can be increased.

[0022] The amount of voids (porosity) can be obtained by image analysis. The electronic component 10 is cut in the thickness direction of the underlayer 6 to make thin slices, and the position and direction of the sample are adjusted by TEM-EDX so that the interface between the ceramic body 1 and the underlayer 6 and the interface between the underlayer 6 and the metal layer 8 are approximately horizontal on the observation screen. The image is then enlarged so that most of the image is the underlayer 6, part of the metal layer 8 is on its front surface 6a side, and part of the ceramic body 1 is on its back surface 6b side. Next, all elements (except carbon (C)) contained in the ceramic body 1, the underlayer 6, and the metal layer 8 are detected by EDX analysis, and each EDX image is made into a composite map. A threshold is set so that parts on the composite map where no elements are detected are white, and binarized image processing is performed to determine the area Sw of the white parts contained inside the underlayer 6.

[0023] On the same screen, find the area of ​​the entire base layer 6. On the screen, visually check the thickness of the base layer 6, and select three locations: the part that is thought to be the thickest, the part that is thought to be the thinnest, and a part that is between these two thicknesses. Measure the thickness of the base layer 6 at each location. Average the three thickness measurements to find the average thickness Tave of the base layer 6. On the same screen, measure the total length Ltotal of the underlayer 6 in a direction perpendicular to the visually determined thickness measurement direction. Multiply the average thickness Tave of the underlayer 6 by the total length Ltotal to obtain the total area Stotal of the underlayer 6 on the screen. The porosity is calculated by dividing the area Sw of the white portion by the total area Stotal of the underlayer 6. That is, the porosity can be obtained by the following formula (1). Porosity (%)=Sw / (Ltotal×Tave)×100 =Sw / Stotal × 100 (1)

[0024] If it is difficult to set the threshold value for binarization when calculating the area Sw of the white parts, the EDX image can be visually inspected to identify the shapes of the areas where elements cannot be detected (appear whitish), and their outlines can be traced by hand to calculate the area of ​​each.

[0025] The thickness of the underlayer 6 is preferably 0.1 μm or more and 2 μm or less. When the thickness of the underlayer 6 is within this range, the effect of improving the bonding strength between the metal layer 8 and the ceramic body 1 can be sufficiently exhibited, and part of the metal layer 8 can easily pass through the pores P of the underlayer 6 and reach the interface between the underlayer 6 and the ceramic body 1 (the back surface 6b of the underlayer 6). The thickness of the underlayer 6 is preferably 0.1 μm or more and 1.7 μm or less, and more preferably 0.1 μm or more and 1.3 μm or less. Such a thin underlayer 6 can be formed by using, for example, a sol-gel method.

[0026] Thickness d of the underlayer 6 T(see FIG. 2) is understood as the distance between the ceramic body 1 and the metal layer 8. The thickness of the underlayer 6 can be determined as the thickness measured at the center of the underlayer using a cross-sectional image obtained by exposing a cross-section in the thickness direction of the underlayer 6, observing the exposed cross-section, and analyzing it appropriately as necessary. The cross-sectional image may be an SEM image obtained using a scanning electron microscope (SEM), an SIM image obtained using a scanning ion microscope (SIM), a TEM image obtained using a transmission electron microscope (TEM), or an SEM / SIM / TEM-EDX image obtained by combining any of these with energy dispersive X-ray analysis (EDX). The exposed cross-section may be one obtained by processing an electronic component using a focused ion beam (FIB).

[0027] In a suitable cross-sectional image, visually check the thickness of the underlayer 6, select three locations, the thickest part, the thinnest part, and a part of intermediate thickness, and measure the thickness of the underlayer 6 at each location. The three thickness measurements are averaged to determine the average thickness of the underlayer 6, which is the thickness of the underlayer 6 (corresponding to Tave described above).

[0028] The underlayer 6 may include a base metal and glass. In the underlayer 6, they may exist as a glass region 13 and a base metal region 11 (see FIG. 2). In a cross-sectional view of the underlayer 6 (FIG. 2), when a portion A on the front surface 6a side (the interface side in contact with the metal layer 8) of the underlayer 6 is compared with a portion B on the back surface 6b side (the interface side in contact with the ceramic body 1) of the underlayer 6, it is preferable that the area of ​​the base metal region 11 within the range of portion A is larger than the area of ​​the base metal region 11 within the range of portion B. When comparing this as the "volume ratio of the base metal to glass" (sometimes referred to as the "base metal / glass ratio" in this specification), it is preferable that the base metal / glass ratio in portion A (the portion on the front surface 6a side of the underlayer 6) closer to the metal layer 8 of the underlayer 6 is higher than the base metal / glass ratio in portion B (the portion on the back surface 6b side of the underlayer 6) closer to the ceramic body 1 of the underlayer 6.

[0029] In this specification, the term "part A of the underlayer 6 closer to the metal layer 8" refers to a part A of the underlayer 6 that is located within a thickness d from the interface between the underlayer 6 and the metal layer 8 (the surface 6a of the underlayer 6). A The thickness d is the part within the range specified by A can be appropriately set within a range of 50% or less of the thickness of the underlayer 6, and typically, the thickness d A is the thickness of the underlayer 6, d T It could be 30% of that. The "portion B of the base layer 6 closer to the ceramic body 1" refers to the portion B of the base layer 6 that is located within a thickness d from the interface between the base layer 6 and the ceramic body 1 (the back surface 6b of the base layer 6). B The thickness d is the part within the range specified by B is the thickness d A Typically, the thickness of the underlayer 6 is d T It could be 30% of that.

[0030] The metal / glass ratio in portion A of the underlayer 6 is higher than the metal / glass ratio in portion B, so that a metal layer 8 with high density can be formed. When forming the metal layer 8 by electrolytic plating, the plating layer is formed on the surface of the conductive material (i.e., the base metal region 11 of the base layer 6). If there is a large amount of base metal region 11 on the surface 6a side of the base layer 6, a plating layer of sufficient density and thickness can be formed on the surface 6a of the base layer 6 when electrolytic plating is performed (the effect of improving the plating adhesion amount).

[0031] Usually, when a base layer containing a base metal and glass is formed, the glass components tend to gather on the surface side of the base layer (this is sometimes called "glass floating"). However, in this embodiment, the metal components gather on the surface 6a side of the base layer 6, which is significantly different from conventional methods. In this embodiment, by controlling the temperature of the heat treatment when forming the underlayer 6, it is possible to make the underlayer 6 have a high underlayer metal / glass ratio in portion A located on the front surface 6a side and a low underlayer metal / glass ratio in portion B located on the back surface 6b side. Note that the mechanism by which the underlayer metal / glass ratio can be made to differ in the thickness direction of the underlayer 6 is not clear, but it is presumed that the influence of factors such as the balance between the sintered state of the glass formed by the sol-gel method and the metallized state of the metal salt when the underlayer 6 is formed, and the wettability between the glass and the metal, is involved.

[0032] The "volume ratio of the metal to the glass (base metal / glass ratio)" can be specified as follows. The electronic component 10 is cut in the thickness direction of the external electrodes 9 to form thin slices, and the base layer 6 of the external electrodes 9 is photographed at any position using TEM-EDX. Next, EDX images of the main component of the glass (e.g., Si in the case of silica glass) and the main component of the base metal (e.g., silver) are obtained.

[0033] Next, in the EDX image of the Si element, the thickness d T The thickness of the underlayer 6 is 10 times as large as that of the surface 6a of the underlayer 6. The thickness of the underlayer 6 is 10 times as large as that of the surface 6a of the underlayer 6. The thickness of the underlayer 6 is 10 times as large as that of the surface 6a of the underlayer 6. T 30% of the total area, an image of three regions (1 to 3) is cut out. A threshold is set so that the target element (Si) is white when present, and binarized image processing is performed to determine the area of ​​the white portion included in regions 1 to 3. Next, an image of the same number of regions (3 regions (7 to 10)) is cut out from the back surface 6b side and similarly binarized image processing is performed to determine the area of ​​the white portion included in regions 7 to 10. These areas are proportional to the glass content in each of the portion on the front surface 6a side of the base layer 6 (portion A closer to the metal layer 8 of the base layer 6) and the portion on the back surface 6b side of the base layer 6 (portion B closer to the ceramic body 1 of the base layer 6).

[0034] In the EDX image of Ag element, the thickness d Tis divided into 10 equal parts and numbered from 1 to 10 from the front surface 6a side of the underlayer 6 to the back surface 6b side. A desired range from the front surface 6a side (however, the same range as when the EDX image of the Si element was processed) is selected. In this example, T An image of the first region (30% of the total area, i.e., three regions 1 to 3) is cut out. A threshold is set so that the target element (Ag) is white when present, and binarized image processing is performed to determine the area of ​​the white portion included in regions 1 to 3. Next, an image of the same number of regions (three regions 7 to 10) is cut out from the back surface 6b side, and similarly binarized image processing is performed to determine the area of ​​the white portion included in regions 7 to 10. These areas are proportional to the content of the base metal in each of the portion on the front surface 6a side of the base layer 6 (portion A closer to the metal layer 8 of the base layer 6) and the portion on the back surface 6b side of the base layer 6 (portion B closer to the ceramic body 1 of the base layer 6).

[0035] If it is difficult to set the threshold value for binarization, the EDX image may be visually inspected to identify the shapes of the underlying metal region 11 and the glass region 13, and their outlines may be traced by hand to calculate the area of ​​each.

[0036] The area of ​​Si and the area of ​​Ag in portion A on the front surface 6a of the base layer 6 are defined as S1 and A1, respectively, and the area of ​​Si and the area of ​​Ag in portion B on the back surface 6b of the base layer 6 are defined as S2 and A2, respectively, and the base metal / glass ratio is calculated using the following equations (2) and (3). “Volume ratio of the base metal to the glass in the portion A of the base layer 6 closer to the metal layer 8”, that is, the base metal / glass ratio in the portion A on the surface 6a side of the base layer 6=A1 / S1 (2) "Volume ratio of the base metal to the glass in the portion B of the base layer 6 closer to the ceramic body 1" i.e., the base metal / glass ratio in the portion B on the back surface 6b side of the base layer 6 = A2 / S2 (3) If the following formula (4) is satisfied, it can be confirmed that the base metal / glass ratio in portion A is greater than the base metal / glass ratio in portion B. A1 / S1>A2 / S2...(4)

[0037] It is particularly preferable that the base metal / glass ratio in portion A of base layer 6 closer to metal layer 8 (the surface 6a side of base layer 6) be 50% or more, and when electrolytic plating is performed to form metal layer 8, a denser plating layer can be formed on surface 6a of base layer 6 (effect of improving plating adhesion). If the following formula (5) is satisfied, it can be confirmed that the base metal / glass ratio in portion A is 50% (0.5) or more. A1 / S1>0.5 (5)

[0038] The underlayer 6 includes a base metal region 11 made of a base metal and a glass region 13 made of glass, and in a cross-sectional view as shown in Figure 3, it is preferable that at least two base metal regions 11 and at least two glass regions 13 are arranged alternately on a straight line L drawn along the thickness direction of the underlayer 6. When mounting electronic component 10, heating is performed for solder reflow, and the thermal stress applied at this time may cause cracks to occur in underlayer 6. This is thought to be due to the thermal expansion coefficient of ceramic body 1 and the thermal expansion of the glass that constitutes the matrix of underlayer 6. By arranging glass regions 13 and underlayer metal regions 11 alternately along the thickness direction of underlayer 6, it is possible to alleviate the concentration of stress due to thermal expansion in glass regions 13, and as a result, it is possible to suppress the occurrence of cracks during reflow.

[0039] The base metal is preferably silver. Alternatively, the base metal may be copper. The glass preferably contains silicon atoms, titanium atoms, and zirconium atoms. Also, the metal layer preferably contains one or more selected from the group consisting of nickel, copper, and tin.

[0040] [Manufacturing method] The electronic component 10 of this embodiment can be manufactured, for example, by the following method.

[0041] 1) Preparation of ceramic body 1 First, prepare the ceramic body 1. The ceramic body 1 can be produced by any appropriate method.

[0042] For example, the ceramic material constituting the ceramic body 1 (more specifically, the ceramic portion 3) is not particularly limited, and is not particularly limited as long as it is a ceramic material used in electronic components. Since the electronic component 10 illustrated in FIG. 1(a) is a multilayer capacitor, the ceramic material is a dielectric material, and examples of the ceramic material include BaTiO3, CaTiO3, SrTiO3, CaZrO3, (BaSr)TiO3, Ba(ZrTi)O3, and (BiZn)Nb2O7. If present, the material constituting the internal electrodes 5a and 5b is not particularly limited as long as it is conductive, and examples of the material include Ag, Cu, Pt, Ni, Al, Pd, and Au. The materials constituting the internal electrodes 5a and 5b are preferably Ag, Cu, and Ni.

[0043] The ceramic material used in this embodiment is not limited to the above-mentioned materials, and may be appropriately selected depending on the type, configuration, etc. of the electronic component. For example, when the electronic component is a ferrite coil component, the ceramic material may be a ferrite material containing Fe, Ni, Zn, Mn, Cu, etc. In this case, the ceramic body may be provided with a coil instead of an internal electrode. As long as the coil is ultimately electrically connected to the external electrode, the coil may be embedded in the ceramic body in advance, or may be wound around the ceramic body before or after the external electrode is formed.

[0044] 2) Formation of Underlayer 6 Next, the underlayer 6 is formed in a predetermined area of ​​the ceramic body 1 where the external electrodes 9 are to be formed.

[0045] In this embodiment, the underlayer 6 can be formed by a thin film preparation method using a solution. Examples of thin film preparation methods include the sol-gel method, the MOD (metal organic compound decomposition method), and the CSD (chemical solution deposition) method. These methods are often treated as synonyms. The term "sol-gel method" used in this specification includes the narrow definition of the "sol-gel method," MOD, and CSD, unless otherwise specified. By using the sol-gel method, it is easy to form a thin film having a thickness of 0.1 μm or more and 2.0 μm or less.

[0046] When the underlayer 6 is formed by using the sol-gel method, a raw material composition is prepared for forming the underlayer 6. The raw material composition may be a liquid (paste) in which a glass raw material (glass precursor), a raw material for the underlayer metal (metal salt), and an organic polymer are dissolved or dispersed in a solvent.

[0047] [Glass precursor] The glass precursor is a glass raw material, and may be any starting material capable of producing a glass matrix (glass region 13). Examples of glass precursors include metal alkoxides, acetylacetonate complexes, acetates, and the like. These raw materials may also be modified with functional groups such as long-chain alkyl groups and epoxy groups. Compounds that can be used as glass precursors are described below.

[0048] (Metal alkoxide) The elements for which metal alkoxides can be synthesized include Li, Be, B, C, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Cd, In, Sn, Sb, Cs, Ba, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Hg, Tl, Pb, Bi, Th, Pa, U, and Pu. The alkoxides of these elements can be used as glass precursors.

[0049] Specific examples of metal alkoxides that can be used as glass precursors are given below. Sodium methoxide, sodium ethoxide, calcium diethoxide, lithium isopropoxide, lithium ethoxide, lithium tert-butoxide, lithium methoxide, boron alkoxide, potassium t-butoxide, tetraethyl orthosilicate, allyltrimethoxysilane, isobutyl(trimethoxy)silane, tetrapropyl orthosilicate, tetramethyl orthosilicate, [3-(Diethylamino)propyl]trimethoxysilane, Triethoxy(octyl)silane, Triethoxyvinylsilane, Triethoxyphenylsilane, Trimethoxyphenylsilane, Trimethoxymethylsilane, Butyltrichlorosilane, n-Propyltriethoxysilane, Methyltrichlorosilane, Dimethoxy(methyl)octylsilane, Dimethoxydimethylsilane, Tris(tert-butoxy)silanol, Tris(tert-pentoxy)silanol, Hexadecyltrimethoxysilane, Dipotassium tris(1,2-benzenediolato-O,O′)silicate, Tetrabutyl orthosilicate, Aluminum silicate, Calcium silicate, Tetramethylammonium silicate solution, Chlorotriisopropoxytitanium(IV), Titanium(IV) isopropoxide, Titanium(IV) 2-Ethylhexyl oxide, titanium(IV) ethoxide, titanium(IV) butoxide, titanium(IV) tert-butoxide, titanium(IV) propoxide, titanium(IV) methoxide, zirconium(IV) bis(diethyl citrato)dipropoxide, zirconium(IV) dibutoxide(bis-2,4-pentanedionate),Metal alkoxides such as zirconium(IV) 2-ethylhexanoate, zirconium(IV) isopropoxide isopropanol complex, zirconium(IV) ethoxide, zirconium(IV) butoxide, zirconium(IV) tert-butoxide, zirconium(IV) propoxide, aluminum tert-butoxide, aluminum isopropoxide, aluminum ethoxide, aluminum tri-sec-butoxide, and aluminum phenoxide.

[0050] (acetylacetonate complex) Specific examples of acetylacetonate complexes that can be used as glass precursors are given below. Metal complexes of acetylacetonates such as lithium acetylacetonate, titanium(IV) oxyacetylacetonate, titanium diisopropoxide bis(acetylacetonate), zirconium(IV) trifluoroacetylacetonate, zirconium(IV) acetylacetonate, aluminum acetylacetonate, aluminum(III) acetylacetonate, calcium(II) acetylacetonate, and zinc(II) acetylacetonate.

[0051] (Acetate) Specific examples of acetates that can be used as glass precursors are given below. Acetates such as zirconium acetate, zirconium acetate hydroxide (IV), and basic aluminum acetate.

[0052] (Glass additives) The glass contained in the underlayer 6 may contain additives (hereinafter referred to as "glass additives") such as those exemplified below. The additives may be mixed in the form of powder, fine particles, or nanoparticles.

[0053] Salts of oxoacids such as soda ash (sodium carbonate Na2CO3), sodium bicarbonate (NaHCO3), sodium percarbonate (2Na2CO3·3H2O2), sodium sulfite (Na2SO3), sodium hydrogen sulfite (NaHSO3), sodium sulfate (Na2SO4), sodium thiosulfate (Na2S2O3), sodium nitrate (NaNO3), and sodium sulfite (NaNO2); halogen compounds such as sodium fluoride (NaF), sodium chloride (NaCl), sodium bromide (NaBr), and sodium iodide (NaI); sodium peroxide (Na2O2 ), oxides such as sodium hydroxide (NaOH); inorganic salts such as hydroxides, sodium hydride (NaH), sodium sulfide (Na2S), sodium hydrogen sulfide (NaHS), sodium silicate (Na2SiO3), trisodium phosphate (Na3PO4), sodium borate (Na3BO3), sodium borohydride (NaBH4), sodium cyanide (NaCN), sodium cyanate (NaOCN), and sodium tetrachloroaurate (Na[AuCl4]); organic acid salts such as sodium acetate (CH3COONa) and sodium citrate.

[0054] Inorganic salts such as calcium peroxide (CaO2), calcium hydroxide (Ca(OH)2), calcium fluoride (CaF2), calcium chloride (CaCl2·2H2O), calcium bromide (CaBr2·2H2O), calcium iodide (CaI2·3H2O), calcium hydride (CaH2), calcium carbide (CaC2), calcium phosphide (Ca3P2); calcium carbonate (CaCO3), calcium bicarbonate (Ca(HCO3)2), calcium nitrate (Ca(NO3)2·4H2O), calcium sulfate (CaSO4·2H2O), calcium sulfite (CaSO3), calcium silicate (CaSiO3 or Ca2SiO4), Calcium phosphate (Ca3(PO4)2), calcium pyrophosphate (Ca2O7P2), calcium hypochlorite (Ca[ClO]2), calcium chlorate (Ca(ClO3)2), calcium perchlorate (Ca(ClO4)2), calcium bromate (Ca(BrO3)2), calcium iodate (Ca(IO3)2, H2O), calcium arsenite (Ca3(AsO4)2), calcium chromate (CaCrO4), calcium tungstate (CaWO4), calcium molybdate (CaMoO4), calcium magnesium carbonate (CaMg(CO3)2), hydroxyapatite (Ca5(PO4)3(OH) or Ca 10 Oxoacid salts such as calcium acetate (Ca(CHCOO)2), calcium gluconate (C 12 H 22 CaO 14 ), calcium citrate (Ca3(C6H5O7)2), calcium malate (Ca(C2H4O(COO)2), calcium lactate (C6H 10 CaO6), calcium benzoate (C 14 H 10 CaO4, Calcium stearate (Ca(C 17 H 35 Organic salts such as calcium aspartate (Ca(C4H6NO4)2).

[0055] Lithium carbonate (Li2CO3), lithium chloride (LiCl), lithium titanate (Li2TiO3), lithium nitride (Li3N), lithium peroxide (Li2O2), lithium citrate (Li3C6H5O7), lithium fluoride (LiF), lithium hexafluorophosphate (LiPF6), lithium acetate (C2H3LiO2), lithium iodide (LiI), lithium hypochlorite (ClLiO), lithium tetraborate (Li2B4O7), lithium bromide (LiBr), lithium nitrate (LiNO3), lithium hydroxide (LiOH), lithium aluminum hydride (LiAlH4), lithium triethylborohydride (Li(C2H5)3BH), lithium hydride (LiH), lithium amide (LiNH2), lithium imide (Li2NH), lithium diisopropylamide (C6H 14 LiN or LiN(C3H7)2), lithium tetramethylpiperidide (C9H 18 LiN), lithium sulfide (Li2S), lithium sulfate (Li2SO4), lithium thiophenolate (C6H5LiS), and lithium phenoxide (C6H5LiO).

[0056] Boron triiodide (BI3), sodium cyanoborohydride (NaBH3CN), sodium borohydride (NaBH4), tetrafluoroboric acid (HBF4), triethylborane ((CH3CH2)3B), borax (Na2B4O5(OH)4·8H2O), and boric acid (B(OH)3).

[0057] Potassium arsenide (K3As), potassium bromide (KBr), potassium carbide (K2C2), potassium chloride (KCl), potassium fluoride (KF), potassium hydride (KH), potassium iodide (KI), potassium triiodide (KI3), potassium azide (KN3), potassium nitride (K3N), potassium superoxide (KO2), potassium ozonate (KO3), potassium peroxide (K2O2), potassium phosphide (K3P), potassium sulfide (K2S), potassium selenide (K2Se), potassium telluride (K2Te), potassium tetrafluoroaluminate (KAlF4), potassium tetrafluoroborate (KBF4), potassium tetrahydroborate (KBH4), potassium methanide (KCH3), potassium cyanide (KCN), potassium formate (KHCOO), potassium hydrogen fluoride (KHF2), potassium tetraiodomercurate(II) (K2[HgI4]), potassium hydrogen sulfide (KHS), potassium octachlorodimolybdate(II) (K4[Mo2Cl8]), potassium amide (KNH2), potassium hydroxide (KOH), potassium hexafluorophosphate (KPF6), potassium carbonate (K2CO3), potassium tetrachloroplatinate(II) (K2[PtCl4]), potassium hexachloroplatinate(IV) (K2[PtCl6]), potassium nonahydrido rhenate(VII) (K2[ReH9]), potassium sulfate (K2SO4), potassium acetate (CH3COOK), potassium cyanide gold(I) (K[Au(CN)2]), potassium hexanitrocobaltate(III) (K3[Co(NO2)6]), potassium hexacyanoferrate(III) (K3[Fe(CN)6]), potassium hexacyanoferrate(II) (K4[Fe(CN)6]), potassium methoxide (KOCH3), potassium ethoxide (KOCH2CH3), potassium tert-butoxide (KOC(CH3)3), potassium cyanate (KOCN), potassium fulminate (KONC), potassium thiocyanate (KSCN), potassium aluminum sulfate (AlK(SO4)2), potassium aluminate (KAlO2), potassium arsenate (K3AsO4), potassium bromate (KBrO3), potassium hypochlorite (KClO), potassium chlorite (KClO2), potassium chlorate(KClO3), potassium perchlorate (KClO4), potassium carbonate (K2CO3), potassium chromate (K2CrO4), potassium dichromate (K2Cr2O7), potassium tetrakis(peroxo)chromate(V) (K3Cr(O2)4), potassium cuprate(III) (KCuO2), potassium ferrate (K2FeO4), potassium iodate (KIO3), potassium periodate (KIO4), potassium permanganate (KMnO4), potassium manganate (K2MnO4), potassium hypomanganate (K3MnO4), potassium molybdate (K2MoO4), potassium nitrite (KNO2), potassium nitrate (KNO3), tripotassium phosphate (K3PO4), potassium perrhenate (KReO4), potassium selenate (K2SeO4), potassium silicate (K2SiO3), potassium sulfite (K2SO3), potassium sulfate (K2SO4), potassium thiosulfate (K2S2O3), potassium disulfite (K2S2O5), potassium dithionate (K2S2O6), potassium disulfate (K2S2O7), potassium peroxodisulfate (K2S2O8), potassium dihydrogen arsenate (KH2AsO4), dipotassium hydrogen arsenate (K2HAsO4), potassium bicarbonate (KHCO3), potassium dihydrogen phosphate (KH2PO4), dipotassium hydrogen phosphate (K2HPO4), potassium hydrogen selenate (KHSeO4), potassium bisulfite (KHSO3), potassium hydrogen sulfate (KHSO4), and potassium hydrogen peroxosulfate (KHSO5).

[0058] Barium sulfite (BaSO3), barium chloride (BaCl2), barium chlorate (Ba(ClO3)2), barium perchlorate (Ba(ClO4)2), barium peroxide (BaO2), barium chromate (BaCrO4), barium acetate (C4H6O4Ba), barium cyanide (Ba(CN)2), barium bromide (BaBr2), barium oxalate (BaC2O4), barium nitrate (BaN2O6), barium hydroxide (Ba(OH)2), barium hydride (H2Ba), barium carbonate (BaCO3), barium iodide (BaI2), barium sulfide (BaS), barium sulfate (BaSO4).

[0059] Metal oxides such as sodium oxide (Na2O), calcium oxide (CaO), lithium oxide (Li2O), boron oxide (B2O3), potassium oxide (K2O), barium oxide (BaO), silicon oxide (SiO2), titanium oxide (TiO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), zinc oxide (ZnO), and magnesium oxide (MgO).

[0060] [Metal salts] The metal salt is a raw material for the base metal, and may be any starting material capable of producing the base metal region 11. Examples of the metal salt include nitrates and carboxylates, and preferably nitrates are used. The metal in the metal salt is not particularly limited and may be appropriately selected depending on the above-mentioned metal material. The metal salt may be one type of metal salt or a mixture of two or more types of metal salts. The metal salt may be solvated, for example hydrated. When the base metal is silver, a silver salt is used as the metal salt.As the silver salt, for example, silver nitrate, silver azide, disilver monofluoride, silver monoxide, silver chloride, silver chlorate, silver perchlorate, silver chromate, silver acetate, silver oxide, silver cyanide, silver cyanate, silver bromide, silver bromate, silver hydroxide, silver carbonate, silver thiocyanate, silver tetrafluoroborate, silver trifluoromethanesulfonate, silver fluoride, silver iodide, silver iodate, silver sulfide, silver sulfate, and silver phosphate are suitable.In addition, silver nanoparticles can be used instead of silver salt.

[0061] [Organic polymer] The organic polymer is used to increase the viscosity of the raw material composition to make it paste-like. Examples of the organic polymer include homopolymers or copolymers of acrylic acid, methacrylic acid, or their esters, specifically acrylic acid ester copolymers, methacrylic acid ester copolymers, acrylic acid ester-methacrylic acid ester copolymers, etc.), polyvinyl acetal (specifically polyvinyl acetal, polyvinyl butyral, etc.), cellulose (specifically hydroxypropyl cellulose, cellulose ether, carboxymethyl cellulose, acetyl cellulose, acetyl nitrocellulose, etc.), polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, polypropylene carbonate, polyvinyl pyrrolidone, etc., and at least one selected from these is included.

[0062] [solvent] The solvent is preferably an alcohol-based solvent (specifically, ethanol vapor pressure 5.9 kPa, 2-propanol 4.3 kPa, 1-butanol 0.6 kPa, etc.), or a glycol ether-based solvent (specifically, propylene glycol dimethyl ether 7.6 kPa, ethylene glycol dimethyl ether 6.4 kPa, propylene glycol monomethyl ether 0.89 kPa, ethylene glycol monomethyl ether 0.83 kPa, diethylene glycol monomethyl ether 0.83 kPa, ethylene glycol monomethyl ether 0.83 kPa, 2-methoxyethanol 0.82 kPa, ethylene glycol monoethyl ether 0.5 kPa, ethylene glycol monomethyl ether acetate 0.27 kPa, etc.). These solvents have a vapor pressure of 0.1 kPa or more at room temperature, and particularly solvents with a vapor pressure of 0.5 kPa or more are suitable. These have a higher vapor pressure than other solvents commonly used in pastes. Incidentally, the solvents described in Patent Document 1 are butyl carbitol acetate 0.0053 kPa and ethyl carbitol 0.013 Pa. Therefore, by using such a solvent, a raw material composition in which the polymer is in an uneven state is obtained. This is because the solvent is easily volatile, and the fluidity is quickly lost between application and drying. In addition, if the paste dries too easily, the life of the paste is shortened, so a solvent with a vapor pressure of less than 0.1 kPa may be appropriately mixed in consideration of productivity. When this raw material composition is applied to a predetermined area of ​​the ceramic body 1 as described below and dried, a coating film in which the polymer is in an unevenly dispersed state is obtained. When this coating film is heated, the unevenly dispersed organic polymer is gasified, and then the glass is melted, thereby forming a base layer 6 having pores penetrating from the front surface to the back surface.

[0063] [Other components (reactants, additives)] The raw material composition may contain any appropriate reactants and additives in addition to glass raw materials (and optional glass additives), metal salts, and solvents. Examples of reactants for obtaining a compound having a structure represented by the formula -OMO- (M is a metal atom) as the main skeleton by reacting a metal alkoxide include water and hydroxyl group-containing compounds capable of substituting alkoxy groups of the metal alkoxide with hydroxyl groups. Examples of additives include catalysts for promoting such reactions, viscosity adjusters, pH adjusters, stabilizers, and the like.

[0064] Next, the raw material composition is applied to a predetermined region of the ceramic body 1 and appropriately dried to form a coating film derived from the raw material composition. The application method is not particularly limited, and immersion, spraying, screen printing, brushing, inkjet printing, etc. can be used. Drying is carried out so that most of the solvent in the raw material composition, preferably substantially all of it, is removed. More specifically, drying can be carried out by heating the ceramic body to which the raw material composition has been applied at 25 to 200°C for 5 to 60 minutes, for example.

[0065] Next, the ceramic body with the coating film is subjected to a heat treatment to obtain the underlayer 6 derived from the coating film. The temperature and time of the heat treatment can be, for example, from 300° C. to 900° C., for example, for 10 to 60 minutes. In particular, the heat treatment temperature is preferably 300°C or higher and lower than 835°C, which allows the base metal / glass ratio of underlayer 6 to be large in portion A on the front surface 6a side and small in portion B on the back surface 6b side. The heat treatment temperature is more preferably 300°C or higher and 800°C or lower, which allows the base metal / glass ratio in portion A on the front surface 6a side of underlayer 6 to be 50% or higher. The heat treatment temperature is particularly preferably 400°C or higher and 750°C or lower.

[0066] During this heat treatment (and, if applicable, during the drying and heating treatments), the raw material composition gels to form the underlayer 6 as a sol-gel fired film. More specifically, as a result of the heat treatment, a glass matrix (glass region 13) is formed from a glass precursor, and an underlayer metal region 11 is formed from a metal material formed from a metal salt.

[0067] The underlayer 6 thus formed by the sol-gel method has pores P that communicate from the front surface to the back surface (the interface with the ceramic body 1). Furthermore, such underlayer 6 is sufficiently thinner than underlayers formed using conventional conductive pastes, and a thin underlayer 6 having a thickness of, for example, 0.1 μm or more and 2 μm or less can be formed.

[0068] Furthermore, by using such a sol-gel method, it is possible to form an underlayer 6 in which the underlayer metal / glass ratio in portion A, which is closer to the metal layer 8 of the underlayer 6, is higher than the underlayer metal / glass ratio in portion B, which is closer to the ceramic body 1 of the underlayer 6 (see FIG. 2). Therefore, when the metal layer 8 is formed by electrolytic plating, a metal film 8 (plated layer) of sufficient density and thickness can be formed on the surface 6a of the underlayer 6.

[0069] 3) Formation of metal layer 8 Next, a metal layer 8 is formed on the underlayer 6 obtained above.

[0070] The metal layer 8 is preferably formed by electrolytic plating, which allows a high density of metal material to be present on the surface 6a side of the base layer 6. Furthermore, since the plating solution can be permeated into the entire pores P of the base layer 6, a plating layer can be formed inside the pores P. In other words, the metal layer 8 can be formed on the surface of the base layer 6, and a part of the metal layer 8 can pass through the pores P and reach the back surface 6b of the base layer 6 (the interface with the ceramic body 1). Furthermore, since the plating layer can be formed in most of the interior of the pores P, it is easy to keep the voids inside the base layer 6 to 1.5 volume % or less.

[0071] The electrolytic plating can be carried out by immersing the ceramic body 1 having the underlayer 6 formed thereon in a plating solution (plating bath) and carrying out a plating process under predetermined conditions. The plating solution used and the plating conditions can be appropriately selected depending on the type of metal to be plated, the thickness of the plating film, etc.

[0072] As described above, when the base metal / glass ratio in portion A of base layer 6 is higher than the base metal / glass ratio in portion B, a plating layer of sufficient density and thickness can be formed on surface 6a of base layer 6 when electrolytic plating is performed, thereby improving the adhesion of metal layer 8.

[0073] In this way, the electronic component 10 of the present embodiment can be manufactured.

[0074] Although one embodiment of the present invention has been described above, the present invention is not limited to this embodiment and various modifications are possible. EXAMPLES

[0075] In the following examples and comparative examples, it is assumed that the electronic component is a multilayer inductor, and a ceramic body for a multilayer inductor is used, but these results are similarly applicable to other electronic components.

[0076] Example 1 1) Preparation of ceramic body 41 First, a ceramic body 41 for a laminated inductor 40 was prepared (see FIG. 4(a)). The ceramic body 41 included a ceramic part 43 made of a ferrite material, a coil conductor 44 wound in a coil shape inside the ceramic part 43, and lead-out portions (internal electrodes 45a, 45b) of the coil conductor 44. The dimensions of this ceramic body 41 were length = 0.60 mm, width = 0.30 mm, and height = 0.30 mm.

[0077] 2) Formation of the underlayer 46 A raw material composition (paste) was prepared by mixing the raw materials (components) shown in "Example 1" in Table 1 in a predetermined mass. The paste contains Si alkoxide (TEOS: tetraethyl orthosilicate), Ti alkoxide (TiBu: titanium butoxide), and Zr alkoxide (ZrPr: zirconia propoxide) as glass precursors. 0.01N-HCl (0.01N hydrochloric acid aqueous solution) functions as an acid catalyst and water for hydrolysis, and HPC (hydroxypropyl cellulose) functions as a viscosity modifier and stabilizer. Next, the raw material composition was applied to both ends of the ceramic body 41 (both end faces and parts of the side faces located in the vicinity thereof) and dried at 150°C for 30 minutes in an air atmosphere (normal pressure) to form a coating film derived from the raw material composition.

[0078] [Table 1]

[0079] Thereafter, the ceramic body 41 with the coating film was subjected to a heat treatment at 635° C. for 30 minutes in an air atmosphere (normal pressure) to form a base layer 46 derived from the coating film (see FIG. 4(b)).

[0080] 3) Formation of metal layer 48 Using the resulting ceramic body 41 with the underlayer 46, a Ni metal layer was formed as a metal layer 48 on the underlayer 46 by electrolytic plating (see FIG. 4(b)).

[0081] This resulted in a sample having external electrodes 49a, 49b, each composed of a base layer 46 and a metal layer 48 formed thereon, on the surface of the ceramic body 41. The external electrodes 49a, 49b covered both ends of the ceramic body 41 (both end faces and parts of the side faces in the vicinity thereof).

[0082] ·evaluation The samples obtained according to this example were evaluated as follows.

[0083] A SEM device was used to observe the cross section of the sample of this example (heat treatment temperature: 635° C.). The obtained SEM image (FIG. 5) confirmed that the thickness of the underlayer 46 was 109 nm. While the thickness of the underlayer formed using a commercially available silver paste as the conductive paste can be about 10 μm, the underlayer 46 in the sample of this example could be thinned to about 1 / 90 of that thickness.

[0084] Using a TEM-EDX device (FE-TEM / EDX (JEOL JEM-F200 (manufactured by JEOL Ltd.) / analysis system Noran system 7 (manufactured by Thermo Fisher Scientific))), the sample of this example (heat treatment temperature: 635°C) was processed to expose a cross section in the thickness direction of the underlayer 46, and the exposed cross section was observed and analyzed. The obtained STEM image is shown in FIG. 5, and TEM-EDX images of Si, Ag and Ni are shown in FIGS. 6 to 8, respectively. In FIGS. 5 to 8, the lower side is the internal electrodes 45a, 45b of the ceramic body 41, and the upper side is the Ni metal layer 48.

[0085] As can be seen from the TEM-EDX image (Si) of the underlayer 46 shown in Fig. 6, the area of ​​the glass region (Si) in the underlayer 46 decreases from the ceramic body 41 side (the internal electrodes 45a, 45b side) toward the metal layer 48 side. Conversely, as can be seen from the TEM-EDX image (Ag) of the underlayer 46 shown in Fig. 7, the area of ​​the underlayer metal region (Ag) increases from the ceramic body 41 side (the internal electrodes 45a, 45b side) toward the metal layer 48 side. Therefore, it was found that the underlayer metal / glass ratio in the portion of the underlayer 46 closer to the metal layer 48 was higher than the underlayer metal / glass ratio in the portion of the underlayer 46 closer to the ceramic body 41 (the internal electrodes 45a, 45b). Although the internal electrodes 45a, 45b and the underlying metal region are both made of Ag, their interfaces could be clearly distinguished from the EDX of the glass (Si).

[0086] 8, it was confirmed that Ni metal layer 48 was formed on the surface of underlayer 46, and that a part of metal layer 48 spread through underlayer 46 to reach the interface between underlayer 46 and ceramic body 41. The Ni metal layer spreading into underlayer 46 spreads so as to fill in the portions where pores in underlayer 46 had existed, which shows that underlayer 46 had pores before Ni metal layer 48 was formed. In addition, since Ni metal layer 48 reaches from the surface of underlayer 46 (interface with the metal layer) to the interface between underlayer 46 and ceramic body 41, it is also shown that the pores in underlayer 46 were connected from the surface of underlayer 46 to the interface with ceramic body 41.

[0087] Since a portion of the Ni metal layer 48 reaches from inside the pores of the underlayer 46 to the interface with the ceramic body 41, the Ni metal layer 48 and underlayer 46 are firmly bonded, and it can be said that the Ni metal layer 48 does not easily peel off from the underlayer 46 (the bonding strength between the metal layer 48 and underlayer 46 is high).

[0088] (Examples 2 to 6, Comparative Examples 1 to 2) Except for preparing the raw material composition according to "Example 1 other than Example 1" in Table 1 and setting the heat treatment temperature to the temperature shown in Table 2, underlayer 46 was formed on the surface of ceramic body 41 to obtain samples in the same manner as in Example 1 (Examples 2 to 6, Comparative Examples 1 and 2). SEM images of the exposed surface of underlayer 46 obtained by heat treatment at each treatment temperature are shown in Figs. 9 to 15.

[0089] For the samples obtained according to Examples 2 to 6 and Comparative Examples 1 and 2, the film thickness and electrical resistance of the underlayer 46 were measured. Furthermore, a Ni metal layer 48 was formed on the surface of the underlayer 46 of each sample by electrolytic plating, and the formability of the electrolytic plating, the state of the metal layer 48 (whether part of the metal layer 48 reached the back surface of the underlayer 46), and the porosity of the underlayer 46 were investigated. The results are shown in Table 2. In Table 2, "-" means "not measured."

[0090] The electrical resistance of the sample was measured by applying the prepared paste to a ceramic substrate by spin coating or the like, firing the substrate, and then measuring the resistance with a digital multimeter at a distance of 0.5 mm between the terminals. As the gap decreased, the electrical resistance decreased.

[0091] In "Formation of electrolytic plating," an evaluation was made as to whether or not a Ni metal layer 48 could be formed by electrolytic plating on the surface of the underlayer 46. An "O" in the table indicates that plating was possible. Note that even if the electrical resistance of the sample was low, at a heating temperature of 150°C, the resin added to adjust viscosity and provide stability remained, and adhesion between the underlayer 46 and the Ni metal layer 48 could not be ensured, so peeling occurred due to the tensile stress of the plating. An "X" in the table indicates that plating was not possible because resistance could not be ensured.

[0092] The state of the metal layer 48 (whether a part of the metal layer 48 reaches the rear surface of the base layer) was determined by forming a Ni metal layer 48 on the surface of the base layer 46, processing it to expose a cross section of the base layer 46 in the thickness direction, and observing STEM images and TEM-EDX images of the exposed cross section, as in Example 1.

[0093] In addition, after forming a Ni metal film 48 on the surface of the underlayer 46, the porosity of the underlayer 46 was determined. The porosity was determined by the method described above. The elements subjected to EDX analysis were oxygen (O), aluminum (Al), silicon (Si), titanium (Ti), iron (Fe), nickel (Ni), zinc (Zn), zirconium (Zr), silver (Ag) and tin (Sn).

[0094] The adhesion between the underlayer and the metal layer was evaluated as follows. A Ni metal layer 48 was formed on the surface of the underlayer 46. The surface of the metal layer 48 was then bonded to the surface of the test substrate with an adhesive, with the surface of the metal layer 48 being the adhesive surface. Next, the sample was pressed (i.e., shear force was applied) in a direction parallel to the surface of the test substrate, and the applied pressure (shear force) when the metal layer 48 peeled off from the underlayer 46 was determined to confirm the peel strength (N). A peel strength of 5N or less was evaluated as NG (×), and a peel strength of 5N or more was evaluated as G (◯).

[0095] [Table 2]

[0096] Consider the results in Table 2. In Examples 2 to 6, the heating temperature was appropriate, so that a part of the metal layer 48 reached the rear surface of the underlayer 46, and therefore the adhesion between the underlayer 46 and the metal layer 48 was good. On the other hand, in Comparative Examples 1 and 2, the heating temperature was not appropriate, so that the metal layer 48 did not reach the rear surface of the underlayer 46, and therefore the adhesion between the underlayer 46 and the metal layer 48 was insufficient.

[0097] (Example 7, Comparative Example 3) In Example 7, the sample after baking the underlayer 46 in Example 1 was used to perform Ni plating under the conditions shown in FIG. 16 to form a Ni plating film (Ni metal layer 48). The relationship between the integrated current and the film thickness of the Ni metal layer 48 was evaluated. In Comparative Example 3, Ni plating was performed on a sample in which a base electrode was formed using a general silver paste (73 wt% Ag particles, 4 wt% glass frit (ZnO-B2O3-SiO2), 10 wt% ethyl cellulose, 13 wt% 1:1 mixture of butyl carbitol acetate and ethyl carbitol). As can be seen from FIG. 16, even in the case of the same integrated current, it was found that the film thickness of the Ni plating film (Ni metal layer 48) in Example 7 was larger than that of the plating film in Comparative Example 3. From this, it was found that Example 7 had a large underlayer metal / glass ratio.

[0098] This application claims priority to Patent Application No. 2021-054076, filed in Japan on March 26, 2021, the entire contents of which are incorporated herein by reference. [Explanation of symbols]

[0099] 1, 41 Ceramic body 3, 43 Ceramic section 5a, 5b, 45a, 45b internal electrode 6, 46 Base layer 8, 48 metal layer 9, 9a, 9b, 49a, 49b external electrode 10 Electronic Components (Multilayer Ceramic Capacitors) 11 Base metal area 13 Glass area 40 Electronic Components (Layered Inductors) 44 Coil Conductor

Claims

1. An electronic component comprising a ceramic body and an external electrode provided on a surface of the ceramic body, the external electrode includes a base layer in contact with a surface of the ceramic body, and a metal layer formed on the surface of the base layer, the underlayer has pores extending from a surface thereof to an interface with the ceramic body, a portion of the metal layer extends through the pore to the interface; The voids in the underlayer are 1.5% by volume or less, The electronic component, wherein the metal layer is a plating layer.

2. The base layer includes a base metal and glass, 2. The electronic component according to claim 1, wherein a volume ratio of the base metal to the glass in a portion of the base layer closer to the metal layer is higher than a volume ratio of the base metal to the glass in a portion of the base layer closer to the ceramic body.

3. 3. The electronic component according to claim 1, wherein the underlayer has a thickness of 0.90 μm or more and 1.59 μm or less.

4. An electronic component as described in claim 2, wherein the volume ratio in the portion of the base layer closest to the metal layer is 50% or more.

5. the underlayer includes a metal underlayer region made of the metal underlayer and a glass region made of the glass, 5. The electronic component according to claim 2, wherein at least two of the base metal regions and at least two of the glass regions are alternately arranged on a straight line drawn in a thickness direction of the base layer in a cross-sectional view.

6. the underlying metal is silver; the glass comprises silicon atoms, titanium atoms, and zirconium atoms; The electronic component according to claim 2 , wherein the metal layer contains at least one selected from the group consisting of nickel, copper, and tin.

7. A method for manufacturing an electronic component including a ceramic body and external electrodes provided on a surface of the ceramic body, comprising the steps of: the external electrode includes a base layer in contact with a surface of the ceramic body, and a metal layer formed on the surface of the base layer, the base layer including a base metal and glass, The method comprises: a step of preparing a raw material composition including a glass precursor as a raw material of the glass, a metal salt as a raw material of the base metal, an organic polymer as a thickener, and a solvent having a vapor pressure of 0.1 kPa or more at room temperature, applying the raw material composition to a surface of the ceramic body, and then performing a heat treatment to form a base layer; and forming the metal layer on the surface of the underlayer by electrolytic plating.

8. The method according to claim 7 , wherein the heat treatment in the step of forming the underlayer is performed at a temperature of 300° C. or higher and lower than 835° C.

Citation Information

Patent Citations

  • Ceramic electronic component

    JP1994215981A

  • Electronic component and method of manufacturing the same

    JP2001244116A

  • Multilayer ceramic electronic component

    JP2013106035A

  • Multilayer ceramic capacitor and method for manufacturing the same

    JP2018032788A

  • Electronic component

    JP2018157183A